2016
DOI: 10.1007/s12020-016-0979-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor suppressor p53 preserves glycation-serum induced pancreatic beta-cell demise

Abstract: Tumor suppressor p53 is a transcriptional factor that determines cell fate in response to multiple stressors, such as oxidative stress and endoplasmic reticulum stress, in the majority of cells. However, its role in pancreatic beta cells is not well documented. Our previous research has revealed that glycation-serum (GS) induced pancreatic beta-cell demise through the AGEs-RAGE pathway. In the present study, we investigated the role of p53 in GS-related beta-cell demise. Using pancreatic islets beta-cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The mouse pancreatic b-cell lines MIN6 and b-TC-6 (passage [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were grown in DMEM (Invitrogen, Grand Island, NY) containing 15% FBS (Gibco, Burlington, Ontario, Canada). The rat pancreatic b-cell line INS-1 (passage 16-30) was cultured in RPMI medium (Invitrogen) containing 10% FBS.…”
Section: Cell Culture and High-glucose And Palmitate Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse pancreatic b-cell lines MIN6 and b-TC-6 (passage [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were grown in DMEM (Invitrogen, Grand Island, NY) containing 15% FBS (Gibco, Burlington, Ontario, Canada). The rat pancreatic b-cell line INS-1 (passage 16-30) was cultured in RPMI medium (Invitrogen) containing 10% FBS.…”
Section: Cell Culture and High-glucose And Palmitate Treatmentmentioning
confidence: 99%
“…TUNEL staining was performed using the In Situ Cell Apoptosis Detection Kit III (fluorescein isothiocyanate) (Boster Biological Technology, Wuhan, Hubei, China), according to the manufacturer's protocol (22). Islets and MIN6 cells were observed under laser scanning confocal microscope (FV1200; Olympus, Tokyo, Japan).…”
Section: Tunel Stainingmentioning
confidence: 99%
“…An elevated level of AGEs is one of the most vivid signs of chronic hyperglycemia, supporting pathogenesis of diabetic complications [ 164 ]. p53 was also found critical for apoptosis of β cells in a glycation-serum-induced mechanism [ 165 ]. Studies performed on INS-1 cells and primary rat islets indicated that transcriptional activity of p53 becomes substantially increased in the presence of glycation serum (GS) and contributes to cell apoptosis.…”
Section: Tissue-specific P53-mediated Changes Triggered By Obesitymentioning
confidence: 99%
“…Since some monogenetic forms of diabetes such as MODY4 also appear to involve apoptotic processes mediated by P53 target genes [83], analyses of DDR activation in MODY patient samples or animal models could further help to understand these rare diseases. In addition, P53 has also been linked to beta cell apoptosis induced by additional mechanisms including hyperglycemia [84] as well as advanced glycation end products [85], and it appears worthwhile to analyze the impact of ATM under these conditions. As a general limitation of our study, our findings are based on acute genetic and pharmacological (but not Cre/loxP or CrispR/Cas9 mediated) manipulation of an immortal rat beta cell line, which shows lower inducibility of glucose stimulated insulin secretion compared to primary beta cells, likely as a compensation for its very high proliferation rate [86].…”
Section: Plos Onementioning
confidence: 99%